Promoting patriotism through mediated sports: Political economy of Bollywood sports movies. Issue 4 (2nd October 2017) - Rasul, Azmat; Proffitt, Jennifer M.
ABSTRACT: Through the lens of political economy of communication and sports, this article examines the role of Bollywood's sports movies in promoting patriotism and constructing an Indian national identity. Focusing on three popular movies premiered in the last decade, Dil Bole Hadippa (2009), Chak De! India (2007), and Lahore (2010), we explicate how Bollywood mobilized patriotic codes through these films in ways that are advantageous for the Indian government and the economic goals of the industry.